Economic Mobility Across Generations in the Developing East Asia and Pacific Region - Narayan, Ambar; Yang, Judy (World Bank, Washington, DC, 2019)
The pace and success of economic growth in the developing East Asia and Pacific region (EAP) has been described as nothing short of a miracle. Education and its complementarities are often linked and credited significantly for the region's positive story on economic growth. During the early stages of the region's development, education kept pace and complemented labor needs; widespread basic literacy and numeracy met demands in manufacturing and assembling. This led to rapid improvements in educational mobility across generations in absolute terms, where mobility is understood as the rise in education levels from one generation to the next. On the other hand, progress has been slower and uneven in relative mobility, which is more closely linked to inequality in education and income and refers to the extent to which an individual's position in society is influenced by that of his or her parents.